2018
DOI: 10.18632/oncotarget.25235
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase 1 and overall survival of patients diagnosed with esophageal cancer

Abstract: BackgroundIndoleamine 2,3-dioxygenase 1 (IDO1) is an enzyme with immunomodulatory properties that has emerged as a potential immunotherapeutic target in human cancer. However, the role, expression pattern, and relevance of IDO1 in esophageal cancer (EC) are poorly understood. Here, we utilize gene expression analysis of the cancer genome atlas (TCGA) and immunohistochemistry (IHC) to better understand the role and prognostic significance of IDO1 in EC.ResultsHigh IDO1 mRNA levels were associated with worse ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…In a previous study, we reported that IDO1 expression was associated with an unfavorable clinical outcome in esophageal cancer. 10 Other studies have also reported on the relationship between IDO1 expression and clinical outcomes in several types of cancer [11][12][13][14][15][16] ( Table 1). However, the molecular mechanisms that regulate IDO1 expression are not completely understood, including in esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported that IDO1 expression was associated with an unfavorable clinical outcome in esophageal cancer. 10 Other studies have also reported on the relationship between IDO1 expression and clinical outcomes in several types of cancer [11][12][13][14][15][16] ( Table 1). However, the molecular mechanisms that regulate IDO1 expression are not completely understood, including in esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, blocking of PD-L1/PD-1 is effective in the treatment of ESCC. However, the prognostic value of PD-L1 remains controversial [ 5 , 20 , 21 ]. PD-L1 can be expressed by a variety of cell types including tumor cells and stromal cells; whether PD-L1 expressed by different cells has different prognostic value is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the B7 family molecules correlate with TDO expression in the liver while IDO shows a correlation with PD-L1 stronger than any other B7 family molecules. Correlation of IDO and PD-L1 has been shown in other tumors (55)(56)(57). Preclinical animal model studies also demonstrated that immune checkpoint blocking strategies with IDO targeting show an enhanced anti-tumor responses (58,59).…”
Section: Discussionmentioning
confidence: 90%